The Impact of Family Violence on Juvenile Delinquency and the Role of Social Work to Reduce it (A descriptive study applied on the observation and social care home in Taif Governorate) - Al-Amri, Hassan Mohammed Balqith; Katbakhana, Ismail AlSayed Khalil (Journal of Humanities & Social Sciences, 2024)
This study aimed to identify the forms of domestic violence that juveniles are exposed to, identify the impact of domestic violence on juvenile delinquency, identify the role of social service in facing family violence. To achieve the objectives of the study, the social survey method was used, whereby the researcher selected a sample of (50) juveniles enrolled in the Observation and Social Care House in Taif Governorate, using a simple random sample method, as well as (10) social workers, who were selected by the comprehensive enumeration method. The researcher prepared a questionnaire that was directed to the juveniles, and an interview guide that was directed to social workers. The study resulted in a set of results, the most important of which are: The presence of many forms of domestic violence to which juveniles are exposed, which include: physical violence, verbal violence, and emotional violence. As well as the presence of many negative effects of family violence on delinquency of events, such as: the formation of feelings of fear, distraction, the formation of negative attitudes towards society, the increase in the desire for revenge among children, and the emergence of aggressive behavior in them. As for the most important proposals, they were: educating parents about the need to avoid wrong practices and trends in raising children, training parents to apply correct methods of raising children and dealing with them, and using the best methods to spread awareness among members of society about the seriousness of the phenomenon of domestic violence.